Origin-country gender norms, individual work experience, and employment among immigrant women in Sweden - Tibajev, Andrey; Nygård, Olav (Frontiers in Human Dynamics, 2023)
Many Western countries are built on a dual-earner model and have high levels of female labor force participation. Increasing the labor market activity of immigrant women is therefore seen as a key part of immigrant integration. However, female labor force participation (LFP) differs substantially between countries, reflecting differences in work-related gender norms that can continue to influence preferences and behaviors after migration. In this study, we investigate how origin-country gender norms and migrant selection interact to produce post-migration outcomes. Our data shows that immigrant women in Sweden have a higher level of pre-migration work experience than expected based on origin-country female LFP, indicating positive selection. Furthermore, the association between origin-country LFP and post-migration employment varied with work experience. For women without origin-country work experience, origin-country LFP was positively associated with employment in Sweden. For women with origin-country work experience, origin-country LFP however was not associated with higher likelihood of employment in Sweden. Though our focus is on immigrant women, we also include immigrant men in our analysis to test our prediction more thoroughly. For men without origin-country work experience, origin-country LFP was negatively associated with employment in Sweden, while we found no association for men with origin-country work experience. Our results show that migrant selection is a crucial factor in understanding the relationship between origin-country LFP and post-migration labor market outcomes, and that these patterns vary with gender. Policy interventions targeting immigrant women from countries with low female LFP should therefore not assume that women arrive socialized with gender-norms that hinder labor market activity.